Čínská ekonomika po vstupu do WTO - aktuální vývoj - Jurčová, Klára (2008)
China is without any doubt one of the hot topics of today`s world and it is going to stay so in the foreseeable future as well. The European Union is aware of that as all other major players in the world are. They look at China in both awe and fear. Whether the fear is justified or not, is another question. China`s WTO entry was a clear signal for its trading partners that the reforms will go on and that China is going to follow its principals. The year 2006 marked the fifth year of China`s accessions to the WTO. By that time, China became, the world`s fourth-largest economy, the world`s third-largest trading nation after the U.S. and Germany, one of the most popular destinations for foreign direct investment, a major global manufacturing center and, along with the U.S. economy, one of the world`s greatest, if not the greatest, engines of economic growth.